Hubungan Terpaan Iklan dan Persepsi pada Karakteristik Celebrity Endorser dengan Minat Beli Kartu Perdana XL - Tania Dira Harucky; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
In competition among these competitors, XL looks decline from year to year starting from 2014 until 2016. So indirectly XL in terms of product quality has experienced a pretty good development, especially in this period of 3 years, but still despite XL has been trying to increase the quality of the network through ads that are displayed with celebriti endorsernya, can not be said to succeed because in terms of sales alone the decline always occurs in this brand. The purpose of this study is to determine the relationship of advertising exposure and perception on the characteristics of celebrity endorser with the interest to buy XL starter pack. Sampling in this research is accidental sampling. The population in this study is people who have seen TV commercials XL starter. The number of samples researched were 100 respondents aged 18-50 years by using accidental sampling technique. Based on the hypothesis test conducted using data analysis Kendall's Tau-b correlation analysis. The results showed that there was a positive correlation between exposure of advertisement with buying interest of XL starter with significance value 0.000 (<0,01) and Kendall Tau-b correlation of 0.495. It shows that the higher the exposure of advertisement, the higher the interest to buy XL starter pack. Furthermore, there is a positive relationship between the perception on the celebrity endorser characteristic with the interest of buying XL starter with a significance value of 0,000 (<0.01) and the correlation coefficient of 0,529. It shows that the more support the perception on the characteristics of celebrity endorser, the higher the interest to buy XL starter pack. The suggestion is that celebrity endorser should be more emphasized on tagline pronunciation